Secondary metabolites produced by marine actinomycete Streptomyces sp. G246 - Quynh, Do Thi; Huong, Doan Thi Mai; Hieu, Tran Van; Ngan, Truong Bich; Minh, Le Thi Hong; Quyen, Vu Thi; Anh, Nguyen Thi Hoang; Murphy, Brian T.; Cuong, Phan Van (Vietnam Journal of Science and Technology, 2021)
In a recent study, we described two new lavandulylated flavonoids, along with eight known compounds from the culture broth of a Streptomyces sp. (strain G246), isolated from the sponge Halichondria panicea, collected in the sea of Son Tra peninsula (Da Nang). A comparison study was conducted to differentiate between solid and liquid fermentation technique for secondary metabolites production of strain G246. In this paper, we report the isolation and structural characterization of 9 secondary metabolites (1-9) from strain G246 by solid state fermentation. Compound 3 was the only one similarity between these fermentation techniques.